Stimulus from social media influencers to the Portuguese tourism and travel industry in the COVID-19 era - Madureira, Lara Batista (2021)
The way society communicates has gone through huge changes during the years. This has led to a revolution on the process of gather and exchange information by the consumers regarding brands, products and services. Nowadays, any person can express their opinion on their social media accounts and share it with whoever he/she wants on a global scale. It’s here that Social Media Influencers (SMIs) appear, anyone with a considerably large audience on social media can influence many others to take an action. Currently, the Tourism & Travel (T&T) industry is facing unprecedent challenges due to the Covid-19 pandemic, being one of the biggest sectors worldwide, driving socio economic development and job creation is vital for this industry to recover as faster as possible. Many actions are being done to make that happen and one possible great tool are SMIs. Shortly, this research aims to understand if SMIs can boost the T&T industry by showing that a destination and its tourism services/products are safe in this time of fear of travelling due to the pandemic.